Bridging Educational Reform and Faith: Evaluating Kurikulum Merdeka's Compatibility with Islamic Values in Madrasahs - Amalia, Eka Rizki; Dwi Bhakti Indri M; Khoiriyati, Salis; Ummah, Nahdiyatul; Oviani, Mila; Kusumawardhani, Jihan; Umayyah, Ummu (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study explored the implementation of Kurikulum Merdeka (KM) in Indonesian Islamic schools (Madrasahs) by analyzing the compatibility of its implementation with Islamic educational values and its challenges and opportunities. The primary aims are to determine the alignment between KM principles and Islamic education, examine obstacles and recommend ways to effectively implement it in Madrasahs. This research synthesizes several academic articles, government policy documents, historical texts, and literature on curriculum development based on library research methods. Content analysis is used to uncover underlying themes, comparative analysis is used to assess compatibility with the curriculum, and critical evaluation is used to assess KM's impact on Islamic education. One key finding revealed is that the features of KM, such as student-centred learning, critical thinking and the development of student character, correspond well with the holistic goals of Islamic education. Nevertheless, major obstacles exist, such as a lack of teacher preparation, resource gaps, and tensions between KM's flexible approaches and Madrasah's traditional frameworks. Despite these challenges, KM presents opportunities for integrating secular and religious education, fostering inclusivity, and promoting innovative teaching practices. KM holds transformative potential in Madrasahs as it can integrate national education reforms with basic Islamic concepts. That would necessitate personalized teacher training, collaborative policy development and tailoring of curriculum for local contexts. Future research has the potential to yield a longitudinal insight into adoption across diverse demographics in different Islamic educational contexts.